Dampak Parenting Education terhadap Parenting Sense of Competence dalam Mempersiapkan Dewasa Awal Menjadi Orangtua sebagai Upaya Peningkatan Kemandirian dan Kesehatan Mental Keluarga - Putri, Pradiptya Septyani; Widhyastuti, Cahyaning; P. S., Adinda Destia; Stiffany, Luccyana (Jurnal Ilmiah Psikologi (JIPSI), 2023)
In Indonesia, there are still many cases related to feelings of incompetence during the process of raising children or what is usually called parental sense of competence (PSOC). Feelings of incompetence during the parenting process can affect the child's future growth and development. One way to anticipate this is by preparing prospective parents to feel competent in parenting. This research was conducted with the aim of looking at the impact of providing psychoeducation on parenting education on parental sense of competence in early adulthood to prepare them as parents in an effort to increase family independence and mental health. This research used a one group pretest-posttest experimental method, with 49 respondents who had the criteria of early adulthood, not being married and not having children. Data was collected using the PSOC questionnaire adapted from Gibaud-Wallston & Wandersman's PSOC measuring tool with a validity score between 0.25-0.74 (<0.25), and a reliability score of 0.726. The collected data was analyzed using paired sample t-test data analysis techniques with the help of SPSS 27. The results of the test obtained a significance score of 0.036 (<0.05), which means the hypothesis is accepted, namely that there is an impact of parenting education on parenting sense of competence in preparing for early adulthood. become a parent.